2018
DOI: 10.1107/s2052252518005407
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous local order in self-assembled nanoparticle films revealed by X-ray cross-correlations

Abstract: An X-ray cross-correlation study of the self-assembly of soft-shell nanoparticles is presented. It is demonstrated that the assembled films are structurally heterogeneous, with dominant hexagonal and cubic symmetries forming patches of 104–105 particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…1(b) (de Jeu, 2016). Such aggregates may originate from the formation of cracks during drying and are in addition visible by scanning electron microscopy as shown previously (Lehmkü hler et al, 2018).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…1(b) (de Jeu, 2016). Such aggregates may originate from the formation of cracks during drying and are in addition visible by scanning electron microscopy as shown previously (Lehmkü hler et al, 2018).…”
Section: Resultssupporting
confidence: 61%
“…Under these conditions the solutions dry in a well defined volume and the film thickness can be controlled by the AuNP concentration. This way, film thicknesses between approximately 100 and 600 nm are obtained (Lehmkü hler et al, 2018). For each film, 7.5 ml solutions of AuNP with the different ligands and salt content described above were pipetted onto the framed membrane and dried at 338 K.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to small variations in the sample volume and the solvent amount needed for chamber saturation, the absolute time differs from that shown in Figure a. Cross‐correlations of Bragg reflections have been recently demonstrated as a valuable tool to access structural information beyond conventional pair‐correlation as probed in the standard SAXS analysis. Here, Fourier coefficients of the correlation function C(q,Δ)=I(q,ϕ)I(q,ϕ+ΔϕI(q,ϕ)ϕ2I(q,ϕ)ϕ2 are calculated from the 2D diffraction patterns.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30] Upon evaporation of the solvent, AuNP@PEG can form extended solids with locally ordered domains. 31 The addition of salt decreases the solubility of PEG in water and at high salt concentrations, aggregation of the free polymer can occur depending on the type of salt. [32][33][34] Zámbó et al demonstrated that the lower critical solution temperature of AuNP@PEG can be lowered effectively by the addition of K 2 SO 4.…”
mentioning
confidence: 99%